2013
DOI: 10.1155/2013/804042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cr Substitution on Magnetic Properties of Mg Nanoferrites Synthesized by Citrate‐Gel Auto Combustion Method

Abstract: A series of Mg-Cr nanoferrites with the chemical formula MgCr Fe 2− O 4 (0.0 ≤ ≤ 1.0) were synthesized by Citrate-Gel auto combustion method. The formation of single phase cubic spinel structure of the samples was confirmed by X-ray diffraction (XRD) analysis. It is observed that with the increase in the paramagnetic Cr content, the particle size of the ferrite compositions has decreased from 23 nm to 7 nm. Faraday magnetic Susceptibility Balance was used to measure the Magnetic susceptibility of synthesized s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The lattice constant is increasing gradually with Cu content due to the larger ionic radius of the Cu 2+ (0.70 Å) than that of the Mg 2+ (0.65 Å) as shown in Figure 2 and agrees with previous literature (22) . The crystallite size of the synthesized Cu doped Mg-Zn ferrite powders was evaluated with the help of Debye-Scherrer's relation (23) ,…”
Section: X-ray Diffraction Studiesmentioning
confidence: 99%
“…The lattice constant is increasing gradually with Cu content due to the larger ionic radius of the Cu 2+ (0.70 Å) than that of the Mg 2+ (0.65 Å) as shown in Figure 2 and agrees with previous literature (22) . The crystallite size of the synthesized Cu doped Mg-Zn ferrite powders was evaluated with the help of Debye-Scherrer's relation (23) ,…”
Section: X-ray Diffraction Studiesmentioning
confidence: 99%
“…low M s fulfils the criteria of achieving the zero H c , enhancing the superparamagnetic nature thereby making them suitable for application in transformers, inductor cores, recording heads, microwave devices, magnetic shielding etc. [37].…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…Although research data showed that magnesium ferrite and its modified forms were paramagnetic (Raghasudha et al 2013), superparamagnetic (Verma et al 2004a, b;Liu et al 2007;Sasaki et al 2010;Sepahvand and Mohamadzade 2011;Chandradass et al 2012;Sheykhan et al 2012; (Ichiyanagi et al 2007;Maensiri et al 2009;Bamzai et al 2014;Manikandan et al 2014;Samiei et al 2018;Uyanga et al 2020), most of them showed superparamagnetic behavior. The S-shaped magnetization curve as shown in Fig.…”
Section: Iv) Vsmmentioning
confidence: 99%